Synthesis and antitubercular evaluation of 2-iminothiazolidine-4-ones - Samala, Ganesh; Madhuri, Chunduri; Sridevi, Jonnalagadda Padma; Nallangi, Radhika; Perumal, Yogeeswari; Dharmarajan, Sriram (European Journal of Chemistry, 2014)
In the present manuscript, we report synthesis of new 3 and 5 substituted 2-imino thiazolidine-4-ones by three step synthetic protocols from 3-trifluormethyl aniline or 2-amino heterocycle. The compounds were evaluated for in vitro activities against Mycobacterium tuberculosis (MTB) in presence and absence of efflux pump inhibitor, cytotoxicity against RAW 264.7 cells. Among the thirty six compounds, 2-imino-3-(5-nitrothiazol-2-yl)-5-(3,4,5-trimethoxybenzylidene)thiazolidin-4-one (5g) was found to be the most active compound in vitro with MICs of 3.31 µM against log-phase culture of MTB and also non-toxic up to 100 µM. Compound 5g showed minimum inhibitory concentration (MIC) of 0.82 µM against MTB in presence of efflux pump inhibitor verapamil.